Embryonic Growth of Chicks under the Influence of Electric Field - Shafey, T.M.; Al-Batshan, H.A.; Al-Hassan, M.J.; Al-Haidary, A.A.; Al-Faraj, A.; Ghannam, M.M. (International Journal of Poultry Science, 2005)
Eggs from layer-type breeder flocks (Leghorn and Baladi, King Saud University) between 40 and 45 weeks of age were used in 2 trials to study the effects of electric field (EF) during incubation on embryonic growth and egg water loss. The incubator was divided into two compartments for the control and EF treatments. Two aluminum plates were fitted to the inside walls, face to face, in the EF compartment and connected to a step up electric transformer. The level of the EF was 30 kV/m, 60Hz. Eggs were set in an incubator on trays either in the control or EF during 18 d of incubation. EF incubation increased egg weight loss, and embryonic weight when expressed on an absolute value, percentage of egg weight, and daily weight gain by approximately 14.3, 50, 49.4, and 46.2%, in Leghorn, and 9.6, 14.7, 14.6, and 14.9%, in Baladi eggs, respectively. There were significant interactions between incubation treatment and age of the embryo on egg weight loss and embryo weight. EF incubation had significantly higher percentage of water loss and embryo weight at 16 and 14 d of incubation and older in Leghorn eggs, respectively and at 15 d of incubation and older in Baladi eggs, when compared with their counterparts of the control incubation treatment. It was concluded that the exposure of chicken eggs to EF of 30 kV/m, 60Hz, during incubation increased the egg water loss, and embryonic growth.